The Existence of Muhammadiyah in Education to Fulfill The Promise of Independence in East Nusa Tenggara - Amirulah Datuk; Arifin Arifin (Universitas Muhammadiyah Malang, 2024)
This article describes and explains Muhammadiyah's contribution to East Nusa Tenggara. The figure of KH. Ahmad Dahlan, with the Muhammadiyah organization, has answered every need of society, from Islamic renewal to working in the social, preaching, and education sectors. Muhammadiyah has eradicated backwardness, poverty, and ignorance and carried out total resistance against formalism and religious conservatism by breaking down